Splenic vessel bleeding in puerperium: a rare maternal near miss case - Parashar, Meetali; Mehta, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Splenic rupture is a very rare entity during pregnancy and puerperium. It has a very high maternal mortality if not diagnosed and managed in time. Here we are presenting a very rare case of splenic haemorrhage on day 5 lower segment caeserian section which was diagnosed and managed at RIMS, Ranchi, Jharkhand, India.